One-pot green synthesis of BSA-capped O-CQDs as an effective fluorescent sensing platform for sensitive and selective detection of promethazine drug - S. Viji; A. Dinesh; K. Radhakrishnan; L. Srimathi Priya; C. Sivasankari; Madhappan Santhamoorthy; Manikandan Ayyar; V. Mohanavel; Mohamed Hashem; Hassan Fouad; G. Ramachandran; S. Santhoshkumar (Sensing and Bio-Sensing Research)
Reliability in biosensing technologies is crucial for the accurate detection and measurement of target molecules, prompting strategies to minimise non-specific binding events that may result in inaccurate findings. This work reports on bovine serum albumin (BSA)-capped oxygen rich carbon quantum dots (O-CQDs) to improve the accuracy of promethazine sensing. The CQDs were produced utilizing a hydrothermal technique with apple juice as a sustainable carbon source. BSA-Caped O-CQDs improve their biocompatibility and stability in physiological conditions while also reducing non-specific interactions with other biomolecules. Several spectroscopic methods, such as fluorescence, X-ray diffraction (XRD) and Fourier-transform infrared spectroscopy (FTIR), were used to evaluate this enhanced specificity and sensitivity. Obtained results show that BSA-O-CQDs had higher specificity for promethazine Furthermore, their ability to resolve non-specific binding was assessed under simulated physiological backgrounds, demonstrating their promise for robust biosensing applications. This sensor method achieved a high selectivity with LOD of 0.2 μM from range of 10–90 μM indicating its suitability for precise promethazine measurement in environmental samples. The primary advantages of this technique include simplified sample preparation together with economic advantages which make it a critical instrument for public health monitoring as well as cutting-edge pharmaceutical research. Sustainable O-CQDs demonstrate the potential for creating environmentally friendly biosensors.